"مساهمة الثقة التنظيمية في تعزيز الاستغلال المعرفي دراسة حالة: بلدية قمار بولاية الوادي " - ايمان نصبة; امال درداخ; هدى مفتاح; عائشة قحف (university of eloued جامعة الوادي, 2024)
"هدفت هذه الدراسة الى مساهمة الثقة التنظيمية في تعزيز الاستغلال المعرفي، من خلال إسقاط تصورنا هذا على الواقع وفق دراسة حالة بلدية قمار بولاية الوادي، ولتحقيق أهداف الدراسة تم الاعتماد على المنهج الوصفي التحليلي واستخدام استمارة الاستبيان كأداة رئيسية لجمع البيانات، إذ احتوت الاستمارة على محورين أساسين: أولا ادراك مستوى الثقة التنظيمية بأبعادها المتمثلة في (الثقة الرئيس المباشر، الثقة بزملاء العمل، الثقة بالإدارة العليا). أما المحور الثاني فشمل المرحلة النهائية لعمليات ادارة المعرفة والمتمثلة في الاستغلال المعرفي، حيث طبقت على عينة مكونة من 66 موظف في جميع المستويات الإدارية. وقد تم التحقق بشكل منتظم من كافة الافتراضات المقترحة وتوصلنا بأن الثقة التنظيمية ببعديها (الثقة الرئيس المباشر و الثقة بالإدارة العليا) تساهم في تعزيز الاستغلال المعرفي، " "This study aimed to explore the contribution of organizational trust in enhancing knowledge exploitation by applying this concept to the real-world context through a case study of the Guemar Municipality in El Oued province. To achieve the study's objectives, a descriptive-analytical methodology was employed, and a questionnaire was used as the main tool for data collection. The questionnaire consisted of two main sections: first, the perception of the level of organizational trust in its dimensions (trust in the direct supervisor, trust in colleagues, and trust in senior management). The second section included the final stage of knowledge management processes, which is knowledge exploitation. The study was conducted on a sample of 66 employees across all administrative levels. All proposed assumptions were systematically verified, and it was concluded that organizational trust in its dimensions (trust in the direct supervisorand trust in senior management) contributes to enhancing knowledge exploitation. "
Keywords: ثقة التنظيمية، ثقة الرئيس المباشر، ثقة بزملاء العمل، ثقة بالإدارة العليا، استغلال المعرفي، إدارة المعرفة. organizational trust; trust in the direct supervisor; trust in colleagues; trust in senior management; knowledge exploitation; knowledge management.